2018
DOI: 10.1002/jbt.22035
|View full text |Cite
|
Sign up to set email alerts
|

Misregulation of membrane trafficking processes in human nonalcoholic steatohepatitis

Abstract: Nonalcoholic steatohepatitis (NASH) remodels the expression and function of genes and proteins that are critical for drug disposition. This study sought to determine whether disruption of membrane protein trafficking pathways in human NASH contributes to altered localization of multidrug resistance-associated protein 2 (MRP2). A comprehensive immunoblot analysis assessed the phosphorylation, membrane translocation, and expression of transporter membrane insertion regulators, including several protein kinases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…Considering that DPPIV follows the transcytotic route to the apical surface 33,34 whereas BSEP and MRP2 do not 34-36 , the mislocalization of DPPIV suggests a possible disruption of some stage of endocytosis and transcytosis of this cargo molecule in the pericentral hepatocytes. This supports previous findings regarding the misregulation of membrane protein trafficking in NAFLD 37 and prompted us to evaluate whether the integrity of the BC could be affected during the disease progression.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Considering that DPPIV follows the transcytotic route to the apical surface 33,34 whereas BSEP and MRP2 do not 34-36 , the mislocalization of DPPIV suggests a possible disruption of some stage of endocytosis and transcytosis of this cargo molecule in the pericentral hepatocytes. This supports previous findings regarding the misregulation of membrane protein trafficking in NAFLD 37 and prompted us to evaluate whether the integrity of the BC could be affected during the disease progression.…”
Section: Resultssupporting
confidence: 87%
“…Third, and most striking, we observed alterations of the apical plasma membrane of hepatocytes and of the BC network. The pericentral hepatocytes showed mislocalization of DPPIV, pointing towards a dysregulation in apical protein trafficking 37 . Interestingly, not all apical proteins were missorted, suggesting that trafficking defects could be pathway-(transcytosis) and/or cargo-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting this finding and in line with preclinical studies in rodent models, 113 114 altered protein trafficking and mislocalization of MRP2 and MRP3 have been found in NASH patients, further substantiating the concept of microcholestasis in NASH. 115 116 Under cholestatic conditions, hepatocellular transport systems undergo adaptive changes mainly through FXR activation, resulting in downregulation of the BA uptake transporter NTCP, whereas compensatory basolateral efflux increases through OSTα/β, MRP3, and MRP4 bypassing impaired canalicular excretion. 117 118 Zucker rats, a rodent model of NAFLD, show impaired hepatobiliary transport compatible with an underlying cholestatic component.…”
Section: Changes In Ba Homeostasis and Microcholestasis In Nashmentioning
confidence: 99%
“…Similarly, no study has explored the influence of statins on the biliary secretions of individual BA in healthy animals. It is of interest to mention that, despite the significant posttranscriptional modulation of crucial transporters for enterohepatic recycling of BA during NASH, available studies have demonstrated the expression of relevant molecules mainly at the mRNA level [ 24 , 25 , 26 ]. Therefore, the present study characterized concentrations of individual BA in plasma, bile, and feces of mice with NASH induced by 24 weeks of consumption of a high–saturated fat, high-fructose, and high-cholesterol diet (F), with atorvastatin administered during the last three weeks.…”
Section: Introductionmentioning
confidence: 99%